Sugarcane Wasted Fibre as a Sustainable Sound Absorber at Different Thickness - Maridan, Nadia Qasrina; Samsudin, Emedya Murniwaty; Abdullah, Naimmuddin; Kamaruddin, Khairol (Journal of Structural Monitoring and Built Environment, 2025)
Traditional sound absorption panels composed of synthetic materials are advantageous due to their efficacy in reducing noise levels. The utilisation of synthetic materials poses considerable health hazards and environmental issues that require urgent consideration. To reduce the adverse effects of synthetic materials, a feasible option is the utilisation of natural fibres, such as sugarcane bagasse. This study utilised sugarcane bagasse, along with gypsum powder and a bio-adhesive serving as a binder, to create panels of two distinct thicknesses (50 mm and 30 mm). The sound absorption performance was evaluated using an impedance tube test in accordance with BS EN ISO-10534-2:2001-transfer function method, spanning low to high frequencies. Moreover, the noise reduction coefficient is calculated using the formula to assess the sample's sound absorption capability. Results indicate that the sugarcane bagasse panel demonstrates favourable outcomes, particularly at lower frequencies for thicker specimens. The 50-mm-thick sample demonstrates peak sound absorption coefficients (SAC) of 0.82 at 400 Hz, but the 30-mm-thick sample attained a value of 0.69 at 800 Hz. Analysis of linear regression indicates that sound absorption performance enhances with increased sample thickness, as the 50 mm samples exhibit higher noise reduction coefficients (NRC) of 0.39, compared to the 0.36 coefficients of the 30 mm samples. The porous structure of sugarcane fibres enables the trapping of sound waves, hence facilitating noise reduction. switching from synthetic to natural fiber-based sound-absorbing panels, particularly those made from sugarcane bagasse, provides a feasible and sustainable approach to noise reduction across different sectors.